2007
DOI: 10.1108/09649420710726193
|View full text |Cite
|
Sign up to set email alerts
|

Women in management: reflections and projections

Abstract: Purpose -A major barrier to women's progress in management worldwide continues to be the gender stereotyping of the managerial position. The purpose of the paper is to examine how this "think manager -think male" attitude has changed over the three decades since the author's initial research and to consider the implications of the outcomes for women's advancement in management today. Design/methodology/approach -The paper reviews the author's research, first conducted in the 1970s and replicated in the USA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
269
1
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(293 citation statements)
references
References 14 publications
10
269
1
13
Order By: Relevance
“…Men have made the rules (Looman, 2011) and "maleness" is inherent to management (Schein, 2007;McInerney-Lacombe et al, 2008;. Women must and can do their best to fit in: a plethora of guidebooks and "cheery instruction manual(s) for how to navigate modern patriarchy" (Penny, 2014: 1) suggest that a woman's way to the top is through individual effort and smart play (Frankel, 2005;Knaths, 2009;Schneider, 2011;Edelburg 2012;Och and Daniels 2013).…”
Section: Lean Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Men have made the rules (Looman, 2011) and "maleness" is inherent to management (Schein, 2007;McInerney-Lacombe et al, 2008;. Women must and can do their best to fit in: a plethora of guidebooks and "cheery instruction manual(s) for how to navigate modern patriarchy" (Penny, 2014: 1) suggest that a woman's way to the top is through individual effort and smart play (Frankel, 2005;Knaths, 2009;Schneider, 2011;Edelburg 2012;Och and Daniels 2013).…”
Section: Lean Inmentioning
confidence: 99%
“…Banyard (2011: 8) claims that indeed "at some point in human history the concept of female inferiority was woven into the very fabric of how we see ourselves, how we treat each other, and how we organise society." Virginia Schein, work-and organizational psychologist, has confirmed managerial sex typing as a major psychological barrier to the advancement of women ("think manager-think male") and a global phenomenon (Schein, 1973(Schein, , 1975(Schein, , 2001(Schein, , 2007. Recent studies confirmed that women still struggle to break through the "glass ceiling"-a term coined in the 1980s-because of their difficulty in fitting into the prevailing male culture, and as a result are being treated as a minority group (Kaufman, 2008: 8).…”
Section: Lean Inmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Broadbrige and Hearn (2008:44), there still is a masculine gendering of management in most organizations. Moreover, Schein (2007) concludes that the strength and flexibility of the "think manager-think male" attitudes held by men in her study are very persistent across time and national boarder.…”
Section: Introductionmentioning
confidence: 83%
“…Schein (2007) in an overview of women in management worldwide states that the persistent stereotype that associates management with being male is the most important hurdle for women in management in all industrialised countries.…”
Section: Women's Employability and Ictmentioning
confidence: 99%